Determinants of Sharia Stock Prices with Systematic Risk as an Intervening Variable - Jannah, Mukhlishotul; Elsa, Elsa; Nawawi, Ma'mun (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2024)
Investment activities through sharia stock instruments carried out by investors aim to achieve returns in the future. However, in practice, investors find it difficult to assess the movement of sharia stock prices and the risks attached to each selected sharia security. As a consideration for making decisions and investing, the movement of sharia stock prices and systematic risk (stock beta) are constantly changing. Stock price movements and systematic risk (stock beta) are caused by various factors, one of which is the national economic condition, commonly referred to as macroeconomic indicators. The results of the study show that inflation, exchange rates, BI rates and money supply have no significant direct effect on systematic risk. The results of testing stock prices show that inflation and money supply have a direct but insignificant effect on stock prices, while exchange rates, BI rates and systematic risk have a direct and significant effect on stock prices. In addition, the results of the study show that inflation and exchange rates have a significant indirect effect on stock prices, while the BI rate and money supply have an indirect effect on stock prices but are not significant for companies listed on the Jakarta Islamic Index for the 2019-2021 period.